Results of using different types of open osteotomies of the fifth metatarsal bone in Taylor’s deformity - A. N. Tsed; K. G. Iliushchenko; A. K. Dulaev; M. А. Mushkin; E. S. Myznikova; R. V. Gladkov (Вестник хирургии имени И.И. Грекова)
The objective was to evaluate the results of surgical treatment in patients with Taylor’s deformity using various types of open osteotomies, including both widely used techniques (Wilson, Weil) and those rarely applied to the fifth metatarsal bone (slide down).Methods and materials. The authors conducted a retrospective single-center research based on archive data from 2021 to 2024. A total of 71 patients were included, among them 3 (4.2 %) men and 68 (95.8 %) women. Patients were divided into three groups according to the type of osteotomy performed on the fifth metatarsal bone during surgery. In each group, we assessed the correction of deformation by radiographic methods, postoperative complications, changes in pain intensity, and functional outcomes of surgical treatment six months after surgery.Results. After surgeries, all analyzed groups showed a significant reduction in pain severity as measured by the VAS, averaging 3.71±1.10, 3.60±1.10, and 3.41±1.86 points respectively, along with an improvement in functional status as measured by the AO FAS scale, averaging 35.82±11.82, 28.79±10.34, and 32.00±13.70 points. Similar radiological results were observed across groups regarding changes in the M4–M5 intermetatarsal angle, varus deviation correction of the fifth toe, and lateral deviation angle of the fifth metatarsal. The third group demonstrated a trend toward fewer non-unions at the osteotomy site, although further research is needed to statistically confirm any potential advantages of the slide-down osteotomy over classical techniques.Conclusion. The considered open osteotomies are reproducible and safe for clinical use and do not require specialized instruments or consumables. The improved slide-down osteotomy technique proposed by the authors for the fifth ray of the foot yields comparable results to traditional techniques used for this location. This method can be safely employed and serve as an additional tool in the arsenal of surgeons performing reconstructive procedures on the forefoot.